Controlling influence of water and ice on eruptive style and edifice construction in the Mount Melbourne Volcanic Field (northern Victoria Land, Antarctica) - Smellie, J. L.; Rocchi, S.; Di Vincenzo, G. (Frontiers in Earth Science, 2023)
The Mount Melbourne Volcanic Field (MMVF) is part of the West Antarctic Rift System, one of Earth’s largest intra-continental rift zones. It contains numerous small, compositionally diverse (alkali basalt–benmoreite) flank and satellite vents of Late Miocene–Pliocene age (≤12.50 Ma; mainly less than 2.5 Ma). They demonstrate a wide range of morphologies and eruptive mechanisms despite overlapping compositions and elevations, and they occur in a relatively small area surrounding the active Mount Melbourne stratovolcano. The volcanic outcrops fall into several main categories based on eruptive style: scoria cones, tuff cones, megapillow complexes, and shield volcanoes. Using the analysis of lithofacies and appraisal of the internal architectures of the outcrops, we have interpreted the likely eruptive setting for each center and examined the links between the environmental conditions and the resulting volcanic edifice types. Previous investigations assumed a glacial setting for most of the centers but without giving supporting evidence. We demonstrate that the local contemporary environmental conditions exerted a dominant control on the resulting volcanic edifices (i.e., the presence or absence of water, including ice or snow). The scoria cones erupted under dry subaerial conditions. Products of highly explosive hydrovolcanic eruptions are represented by tuff cones. The water involved was mainly glacial (meltwater) but may have been marine in a few examples, based on a comparison of the contrasting internal architectures of tuff cones erupted in confined (glacial) and unconfined (marine, lacustrine) settings. One of the glaciovolcanic tuff cones ceased activity shortly after it began transitioning to a tuya. The megapillow complexes are highly distinctive and have not been previously recognized in glaciovolcanic successions. They are subglacial effusive sequences emplaced as interconnected megapillows, lobes, and thick simple sheet lavas. They are believed to have erupted at moderately high discharge and reduced cooling rates in partially drained englacial vaults under ice, probably several hundred meters in thickness. Finally, several overlapping small shield volcanoes crop out mainly in the Cape Washington peninsula area. They are constructed of previously unrecognized multiple ‘a‘ā lava-fed deltas, erupted in association with a thin draping ice cover c. 50–145 m thick. Our study highlights how effectively water in all its forms (e.g., snow, ice, and any meltwater) or its absence exerts a fundamental control on eruption dynamics and volcano construction. When linked to published ages and 40Ar/39Ar dates produced by this study, the new environmental information indicates that the Late Pliocene–Pleistocene landscape was mainly an icefield rather than a persistent topography-drowning ice sheet. Ice thicknesses also generally increased toward the present.